2021
DOI: 10.1111/nph.17058
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate depletion in roots impedes phosphorus nutrition in young forest trees

Abstract:  Nutrient imbalances cause the deterioration of tree health in European forests, but the underlying physiological mechanisms are unknown. Here, we investigated the consequences of decreasing root carbohydrate reserves for phosphorus (P) mobilization and uptake by forest trees.  In P-rich and P-poor beech (Fagus sylvatica) forests, naturally grown, young trees were girdled and used to determine root, ectomycorrhizal and microbial activities related to P mobilization in the organic layer and mineral topsoil in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 107 publications
1
21
0
Order By: Relevance
“…The experimental design has been previously described in detail by Clausing et al (2021). Briefly, the experiment was conducted at two beech (F. sylvatica L.) forests in Germany, Bad Brückenau (BBR: 5579975 N, 3566195 E) and Luess (LUE: 5857057 N, 3585473 E), with different soil properties.…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental design has been previously described in detail by Clausing et al (2021). Briefly, the experiment was conducted at two beech (F. sylvatica L.) forests in Germany, Bad Brückenau (BBR: 5579975 N, 3566195 E) and Luess (LUE: 5857057 N, 3585473 E), with different soil properties.…”
Section: Experimental Designmentioning
confidence: 99%
“…The results from Clausing et al (2021) and the previously demonstrated importance of gluconic acid for inorganic P solubilization (Goldstein, 1995;Rodríguez and Fraga, 1999;Alori et al, 2017) gave us the motivation to investigate feedback loops of plant-derived C and shifts in the stoichiometry of soil C:P on the diversity of gcd-harboring PSB. For this purpose, we used a molecular barcoding approach based on the gcd gene to assess changes in diversity and community composition in response to P and C availability.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Due to continuously high atmospheric N deposition, phosphorus (P) becomes increasingly important as a limiting element for plant growth and therefore might limit the functioning of the ecosystem (Holland et al 2005;Vitousek et al 2010;Lang et al 2017;Clausing et al 2020). We investigated the availability of P in forest soils by collecting soil samples as described above.…”
Section: Available Phosphorusmentioning
confidence: 99%